Early Effects of the COVID-19 Pandemic on Housing Market in the United States - Baris K. Yörük (Center for Economic Studies and Ifo Institute (CESifo), 2020)
I use daily data from fifty major cities to investigate the early effects of the COVID-19 pandemic on housing market in the United States. I find that starting from the second half of March, 2020, new home listings and pending home sales started to decrease. By mid-April, certain markets experienced more than 60% drop in new home listings and pending home sales relative to the same time period in the previous year. The collapse of the housing market is broad based, hitting all major cities, regardless of the intensity of virus spread or timing of the introduction of state level policies to combat the pandemic. The only exception is the closure of non-essential businesses at certain states, which is associated with up to a 9 percentage point decrease in new home listings.
Keywords: I18; R31; 330; covid-19; housing market; United States